I07 Abnormalities In Weight And Bmi In Children With Juvenile Huntington's Disease. (17th September 2014) - Nopoulos, P; Tereskchenko, A; McHugh, M; Dawson, J; Lockhart, K; Gonzalez, P
Abstract : Background: Abnormalities in weight and BMI have been shown not only in preHD adults, but also preHD children suggesting that metabolic abnormalities may affect body composition with primary effects in skeletal muscle. Growth measures have never been reported in children with Juvenile Huntington's disease (JHD). Methods: Growth measures for 18 JHD subjects were obtained through medical chart review, documented either prior to diagnosis or soon after. These measures were compared to a large sample (n = 274) of healthy developing children, as well as the Centre for Disease Control (CDC) growth norms. Results: After controlling for effects of sex and age, the JHD subjects had no significant differences in height. However, they were an average of 10% lower than normal controls in weight and BMI. Using CDC norms, the JHD subjects had the same pattern of normal height but decrement in weight. Length of CAG repeat was significantly correlated to measures of weight with longer CAG repeats being associated with more severe weight reduction. A subset of 4 subjects had measures that pre-dated onset of any symptom and were therefore preJHD. These subjects also had a significant decrement in BMI compared to CDC norms. Conclusion: Children with JHD have normal height, but significantly reduced weight and BMI, indicating a specific deficit in skeletal muscle growth. As the preJHD subjects were also low in BMI, this suggests that these changes are due directly to the effect of the mutated gene on development, rather than symptom manifestation of the disease itself.